Effects of obstetric factors and storage temperatures on the yield of endothelial colony forming cells from umbilical cord blood. - Coldwell, K; Lee, S; Kean, J; Khoo, C; Tsaknakis, G; Smythe, J; Watt, S (2011)
As umbilical cord blood (UCB) is a rich source of endothelial colony-forming cells (ECFC), our aim was twofold: (1) to examine potential obstetric selection criteria for achieving the highest ECFC yields from UCB units, and (2) to determine whether transient storage temperatures of fresh UCB and cryopreservation of UCB units affected ECFC yield and function. ECFC quality was assessed before and after cryopreservation by their clonogenic proliferative potential. Of the 20 factors examined, placental weight was the only statistically significant obstetric factor that predicted ECFC frequency in UCB. Studies on the effects of storage revealed that transient storage of fresh UCB at 4°C reduced ECFC yield compared with storage at 22°C, while cryopreservation of UCB MNCs significantly reduced ECFC recoveries. To our knowledge, this is the first demonstration that placental weight and temperature of storage prior to processing or culture have significant effects on ECFC frequency in UCB. Our studies further support the evidence that cryopreservation of UCB MNCs compromises ECFC recovery.